2016
DOI: 10.3389/fphys.2016.00332
|View full text |Cite
|
Sign up to set email alerts
|

Similar Inflammatory Responses following Sprint Interval Training Performed in Hypoxia and Normoxia

Abstract: Sprint interval training (SIT) is an efficient intervention capable of improving aerobic capacity and exercise performance. This experiment aimed to determine differences in training adaptations and the inflammatory responses following 2 weeks of SIT (30 s maximal work, 4 min recovery; 4–7 repetitions) performed in normoxia or hypoxia. Forty-two untrained participants [(mean ± SD), age 21 ±1 years, body mass 72.1 ±11.4 kg, and height 173 ±10 cm] were equally and randomly assigned to one of three groups; contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 54 publications
4
33
0
Order By: Relevance
“…In the present study SpO 2 averaged 97% at rest and was maintained between 93-95% during NORM exercise. (Richardson et al 2016). In that study, SpO 2 was maintained at ~97% during sprint interval training in normoxia,…”
Section: Systems-level Physiological Responsesmentioning
confidence: 79%
See 1 more Smart Citation
“…In the present study SpO 2 averaged 97% at rest and was maintained between 93-95% during NORM exercise. (Richardson et al 2016). In that study, SpO 2 was maintained at ~97% during sprint interval training in normoxia,…”
Section: Systems-level Physiological Responsesmentioning
confidence: 79%
“…whereas it progressively decreased (p<0.05) across six WAnT that were performed in hypoxia (from 86% on WAnT 1 to 77% on WAnT 4) (Richardson et al 2016). Despite those large differences in SpO 2 , no differences in HR were shown between groups (Richardson et al 2016).…”
Section: Systems-level Physiological Responsesmentioning
confidence: 91%
“…The greater effort evoked during SIT stimulates a transient metabolic disturbance (i.e., greater O 2 and lactate accumulation), which will promote the activation of signaling proteins necessary for training-induced adaptation ( Gibala et al, 2009 ; MacInnis and Gibala, 2017 ). Also, a SIT session promotes a transient, rich milieu of pro- and anti-inflammatory signaling cytokines, such as interleukins (IL)-6 and IL-10, and tumor necrosis factor (TNF)-α ( Richardson et al, 2016 ), which may induce immune system adaptations to SIT.…”
Section: Introductionmentioning
confidence: 99%
“…However, the chronic effect of SIT on anti-inflammatory status has received limited attention. The few existing studies have reported conflicting results regarding the effects of a brief period of SIT on the exercise-induced inflammatory profile ( Hovanloo et al, 2013 ; Richardson et al, 2016 ). In those studies, 2 weeks of SIT (4–7 × 30-s sprint/240-s rest) either did not affect the late (48 h) post-exercise IL-6 and IL-10 response ( Hovanloo et al, 2013 ) or promoted a greater post-exercise increase in both IL-6 and TNF-α ( Richardson et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results were analyzed for total work (TW), peak power output (PPO), mean power output (MPO), end power output (EPO), time to PPO (Bar-Or, 1987 ). Fatigue index (FI) was determined by taking the percentage difference between PPO and EPO (Richardson et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%